2014
DOI: 10.1017/als.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change And Migration: Law and Policy Perspectives in Bangladesh

Abstract: Global climate change and consequent potential migration pose a number of challenges and are becoming increasingly important policy issues for Bangladesh. Therefore, policy responses need to deal with diverse issues, including sustainable development (SD), adaptation to climate change, and humanitarian assistance, to address the future challenges posed by climate change and consequent human displacement. There is no simple and straightforward solution to the challenges posed by climate-induced migration, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Likewise, the capacity was assessed by using several criteria i.e., present status of local-level Govt. and NGOs structure for disaster management (Azad et al 2019;Seddiky et al 2020;Uddin et al 2020), present status of disaster preparedness plan (Khan 2008;Huq 2016;Islam et al 2021), sound and observed legislation about DRR and disaster preparedness (Banu 2015;Naser 2015;Shahjahan et al 2016), status of diversity of livelihood options in the community (Kamal 2013;Roy and Basu 2020;Sarker et al 2020), existing Govt. resource levels to minimize disaster risk (Khan and Rahman 2007;Afrin 2018), people knowledge level of different hazards (I.…”
Section: Methods For Risk Assessmentmentioning
confidence: 99%
“…Likewise, the capacity was assessed by using several criteria i.e., present status of local-level Govt. and NGOs structure for disaster management (Azad et al 2019;Seddiky et al 2020;Uddin et al 2020), present status of disaster preparedness plan (Khan 2008;Huq 2016;Islam et al 2021), sound and observed legislation about DRR and disaster preparedness (Banu 2015;Naser 2015;Shahjahan et al 2016), status of diversity of livelihood options in the community (Kamal 2013;Roy and Basu 2020;Sarker et al 2020), existing Govt. resource levels to minimize disaster risk (Khan and Rahman 2007;Afrin 2018), people knowledge level of different hazards (I.…”
Section: Methods For Risk Assessmentmentioning
confidence: 99%
“…Article 18A of the Constitution of the People’s Republic of Bangladesh (1972) holds that, ‘the State shall endeavour to protect and improve the environment and to preserve and safeguard the natural resources, bio-diversity, wetlands, forests and wild life for the present and future citizens’. Despite this constitutional duty to protect the environment, the provision ‘does not establish any corresponding rights for displaced people or those who are at risk of displacement due to failures to protect the environment’ (Naser, 2015). Migrants and displaced people need to be mainstreamed in the Bangladesh’s law and policy framework to be afforded appropriate and comprehensive protections by the State and realise this right as recognised by the Bangladesh Constitution.…”
Section: Internal Migration Law and Policy And Its Governance In Bang...mentioning
confidence: 99%
“…The Bangladesh National Adaptation Programme of Action (NAPA) (Ministry of Environment and Forests, 2005) and Bangladesh Climate Change Strategy and Action Plan (BCCSAP) (Ministry of Environment and Forests, 2009) also play an important role in developing strategic responses to the impacts of climate change. The NAPA was developed in 2005 to guide national and international responses to climate risks and to integrate such responses into development plans and processes (Naser, 2015). It provides discussion on adaptation strategies that can be undertaken, including enhancing the resilience of urban infrastructure and industries from the impacts of climate change and preparing vulnerable communities for internal emergencies (Ministry of Environment and Forests, 2005).…”
Section: Internal Migration Law and Policy And Its Governance In Bang...mentioning
confidence: 99%
“…The interest that this issue has raised in the scientific community is such that in the last decade the number of articles which link Climate Change to an increase in migratory movements that are a result of attempts to adapt to the environment [ 8 , 20 , 23 , 29 , 35 , 36 , 38 , 64 ]. Of note are studies carried out in Africa [ 22 , 25 , 39 , 42 , 58 ], Asia [ 12 , 17 , 40 , 56 , 59 , 65 ], America [ 21 , 37 , 41 , 54 , 63 ] and, to a lesser extent, Europe [ 16 , 28 ].…”
Section: Introductionmentioning
confidence: 99%